STUDIES ON THE AIR QUALITY IN A DAIRY PROCESSING PLANT - K. Radha; Lakshmi S. Nath (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Microbial quality of air in a dairy processing plant was evaluated to ascertain the contribution of air as a source of contamination and spoilage of milk and milk products. The mean total aerobic counts obtained in the air by sedimentation method were 32.66 ± 3.82, 25.32 ± 4.17 and 33.36 ± 3.53 cfu/m 2 in raw milk reception dock, pasteurization room and product preparation room respectively. The respective mean total coliform counts were 1.52 ± 0.14, 0.66 ± 0.08 and 0.99 ± 0.16 cfu/ m2. Total coliform count observed in the raw milk reception dock was significantly higher (P< 0.01) than the other areas.  The mean Staphylococcal counts were 2.52 ± 0.10, 3.84 ± 0.31and 5.82 ± 0.30 cfu/ m2. The product preparation room showed highest mean Staphylococcal counts followed by pasteurization room and raw milk reception dock.  The mean yeast and mould counts obtained were 5.42 ± 0.39, 3.84 ± 0.31and 5.82 ± 0.30 cfu/ m2  in raw milk reception dock, pasteurization room and product preparation room respectively. Effect of fumigation on the microbial quality of air in the dairy processing area was also studied by comparing the microbial load in the air before and after fumigation. Fumigation practice followed in the dairy processing area was highly effective against total aerobic organisms, coliforms, and Staphylococci but not very effective in the case of yeast and moulds.